2015
DOI: 10.1002/anie.201504790
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Salts of Anionic Chiral Cobalt(III) Complexes as Catalysts of the Enantioselective Povarov Reaction

Abstract: The sodium salts of anionic chiral cobalt(III) complexes (CCC(-) Na(+) ) have been found to be efficient catalysts of the asymmetric Povarov reaction of easily accessible dienophiles, such as 2,3-dihydrofuran, ethyl vinyl ether, and an N-protected 2,3-dihydropyrrole, with 2-azadienes. Ring-fused tetrahydroquinolines with up to three contiguous stereogenic centers were thus obtained in high yields, excellent diastereoselectivities (endo/exo up to >20:1), and high enantioselectivities (up to 95:5 e.r.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 62 publications
2
46
0
Order By: Relevance
“…[1] Benefiting from the renaissance of visible-light-induced organic photochemistry, which delivers adiverse variety of radical intermediates in an environment-and user-friendly means, [2] exciting developments of catalytic asymmetric radical transformations have been witnessed in the past decade. [5,6] Despite great contributions having been made in this field, exploring chiral octahedral complexes avoiding precious metals and allowing facile steric regulation is still highly desirable. [5,6] Despite great contributions having been made in this field, exploring chiral octahedral complexes avoiding precious metals and allowing facile steric regulation is still highly desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Benefiting from the renaissance of visible-light-induced organic photochemistry, which delivers adiverse variety of radical intermediates in an environment-and user-friendly means, [2] exciting developments of catalytic asymmetric radical transformations have been witnessed in the past decade. [5,6] Despite great contributions having been made in this field, exploring chiral octahedral complexes avoiding precious metals and allowing facile steric regulation is still highly desirable. [5,6] Despite great contributions having been made in this field, exploring chiral octahedral complexes avoiding precious metals and allowing facile steric regulation is still highly desirable.…”
mentioning
confidence: 99%
“…[3,4] Thesearch for efficient chiral catalysts and concepts that are compatible with photochemical processes is obliviously crucial to this notable success.I nt his respect, the Meggers group successfully developed Ir-, Rh-, and Ru-based chiral octahedral complexes, [4] which have impressive catalytic efficiency and stereoinduction capacity in as eries of visible-light-induced asymmetric radical reactions.M ore significantly,t he concept of octahedral metal-centered chirality provided an important cornerstone for steering the development of new chiral organometallic catalysts. [6] Given the excellent stereoinduction of chiral N 4 ligands in asymmetric oxidations by joint use with Fe and Mn salts, [7] here we designed ak ind of novel chiral Co-centered octahedral complexes under the guidance of Meggers concept ( Figure 1a). [6] Given the excellent stereoinduction of chiral N 4 ligands in asymmetric oxidations by joint use with Fe and Mn salts, [7] here we designed ak ind of novel chiral Co-centered octahedral complexes under the guidance of Meggers concept ( Figure 1a).…”
mentioning
confidence: 99%
“…[3,4] Thesearch for efficient chiral catalysts and concepts that are compatible with photochemical processes is obliviously crucial to this notable success.I nt his respect, the Meggers group successfully developed Ir-, Rh-, and Ru-based chiral octahedral complexes, [4] which have impressive catalytic efficiency and stereoinduction capacity in as eries of visible-light-induced asymmetric radical reactions.M ore significantly,t he concept of octahedral metal-centered chirality provided an important cornerstone for steering the development of new chiral organometallic catalysts. [5,6] Despite great contributions having been made in this field, exploring chiral octahedral complexes avoiding precious metals and allowing facile steric regulation is still highly desirable. [6] Given the excellent stereoinduction of chiral N 4 ligands in asymmetric oxidations by joint use with Fe and Mn salts, [7] here we designed ak ind of novel chiral Co-centered octahedral complexes under the guidance of Meggers concept ( Figure 1a).…”
mentioning
confidence: 99%
“…Kinetic studies revealed that optically pure CCC À Na + showed ah igher catalytic activity than ar acemic catalyst sample ( Figure S2), [9] which might be the possible reason for the positive nonlinear effect. [10] According to these experimental data and the crystal structures of CCC À Na + L-4h [11] and the products 3aa and 3ia, [12] we propose at ransition state to explain the observed stereochemistry (Scheme 2). Thes odium cation, in combination with the weakly coordinating chiral anion, is considered to act as aLewis acid to activate 2-azadiene 1a,leading to the possible transition state TS-I,a ss uggested by preliminary DFT calculations.…”
Section: Methodsmentioning
confidence: 74%